O‘ZBEKISTONDA ISLOMIY MOLIYA MUNOSABATLARINI JORIY ETISH: MUAMMO VA ECHIMLAR - Soliyev Dilmurod Jamolovich; Oxunova Dilnavozxon Oybek qizi (MANAGEMENT AND ECONOMICS SCIENTIFIC RESEARCH JOURNAL, 2025)
The article describes the issues and problems of the organisation of Islamic finance in our country. Based on the study of the best practices of foreign countries, proposals for the introduction of Islamic finance in the country are presented.